Article biodiversity inside bottles: animals, fungi, and plants in traditional alcoholic drinks - María Cruz Juárez-Aragón; Yolanda del Rocio Moreno-Ramírez; Reyna Ivonne Torres-Acosta; Jorge Ariel Torres-Castillo; Jorge Ariel Torres-Castillo (Frontiers in Nutrition, 2024)
The use of animals, fungi, and plants as a source of bioactive compounds has been widely practiced in diverse cultures throughout the world, particularly in alcoholic drinks. The nature of the biological material, method of preparation and alcohol concentration play a predominant role in the extraction of bioactive compounds and the achievement of desired results. However, certain aspects must be considered to guarantee the innocuity of these drinks and reduce the risk of intoxication, infections and allergic reactions, aspects which are sometimes overlooked. In addition, the implications of using threatened or protected species must be considered to reduce the negative impact on their populations. The authors recommend the establishment of production systems which guarantee products with adequate quality controls and ensure the benefits to the consumer.